Integrated model for understanding Indian physicians' internet usage pattern: An empirical approach. (2nd January 2017) - Patwardhan, Avadhut Arun; Pandey, Neeraj; Dhume, S. M.
Abstract: Purpose : A recent change in the definition of pharmaceutical promotion allows for incorporation of emerging mediums like internet. Physicians are important stakeholders of the pharmaceutical marketing process. In India, the pharmaceutical promotions are predominantly physician directed in nature as the legal framework does not allow Direct to Consumer Advertising. Therefore, the knowledge about adoption and usage pattern of internet among Indian physician needs to be examined for devising internet-based physician- directed pharmaceutical promotions. In light of these developments, the purpose of this research paper is to empirically test an integrated conceptual model. Using an integrated technology acceptance model, this study examines impact of individual and technological factors that influence physicians' acceptance of internet. Methodology : The non-probabilistic sampling technique, i.e. snowball sampling, was adopted for the study. The survey method was used for collecting the data. Data were collected from general physicians and specialists in the India using a self-administered questionnaire. The relationships proposed in the integrated conceptual model were tested using structural equation modelling (SEM). Findings : The findings of this study indicate that both the individual characteristics (optimism, innovativeness, and discomfort) and technology characteristics (compatibility) influence the perceived beliefs of physicians. Originality and value : This study provides a robust conceptual and empirically tested integrated model and validated instruments for examining physicians' internet adoption behaviour in changing Indian pharmaceutical marketing context.